79 Activity of chemotherapy in recurrent uterine serous carcinoma. (13th November 2020) - Beavers, R; Fellman, B; Eyada, M; Klopp, A; Fleming, N; Lu, K; Soliman, P; Westin, S
Abstract : Background: Uterine serous carcinoma (USC) carries a poor prognosis and the majority of patients develop recurrence. The study objective was to compare efficacy of chemotherapy regimens in recurrent USC. Methods: A retrospective review of patients with USC treated at our institution from 1993 to 2012 was performed. Recurrence-free survival (RFS) was estimated using methods of Kaplan and Meier and modeled via Cox proportional hazards regression. RFS1 was calculated from date of first recurrence to second recurrence. Platinum-sensitivity was defined as recurrence >6 months after platinum-based therapy. Those never exposed to chemotherapy during adjuvant therapy were included in the platinum-sensitive cohort. Results: Of 313 patients, 147 (47%) had recurrence. Median age was 64 years; 65% were stage III/IV. Median follow up was 39.3 months. Median RFS1 was 5.5 months (95% CI 0.7 – 31.4). 115 patients (78%) received chemotherapy alone. Objective response was highest in the platinum-sensitive compared with the platinum-resistant cohort ((21/84; 25%) vs. (4/35; 11%)). In platinum-sensitive disease treated with chemotherapy, platinum-based had higher response compared to non-platinum-based regimens (18/44(41%) vs 3/41(7%) p=0.029). Response in platinum-resistant tumors to platinum-based regimens was 37%(3/8). 86% of patients with platinum-resistance had progressive disease regardless of chemotherapy. 86 patients (27%) had a second recurrence, 47(55%) were platinum-sensitive and 36(77%) were treated with chemotherapy. Response to chemotherapy was 5% in those with a second recurrence. Conclusion: In patients with recurrent USC deemed platinum-sensitive at first recurrence, platinum-based regimens may be associated with improved response. Platinum-resistant tumors do not appear to have an optimal second-line chemotherapy regimen.